Bifurcations and route to chaos for flow over an oscillating airfoil. (July 2018) - Khalid, Muhammad Saif Ullah; Akhtar, Imran; Dong, Haibo; Ahsan, Nida; Jiang, Xiaoping; Wu, Binxin
Abstract: Using immersed boundary methods, we perform numerical simulations for flow over an elliptical airfoil oscillating at a reduced frequency of 6.283 over a range of Strouhal number with Reynolds number 500. We quantify the response of this nonlinear system through time-histories of aerodynamic lift and thrust force coefficients, their Fourier spectra, phase maps, Poincáre sections, and higher-order spectral analysis. When the oscillation amplitude increases, this nonlinear system undergoes bifurcations, thus eventually achieving chaotic solutions. The aerodynamic response moves quasi-periodically through to chaos. We also relate these behavioral changes in the response of the system to the wake transitions. We also present cross-bispectrum between the lift and thrust coefficients, and auto-trispectrum for the lift coefficient to study cubic coupling among various frequency components. We find the strongest quadratic and cubic coupling between the excitation frequency components. We also observe the cubic coupling among various frequency components responsible for generating new harmonics in the spectra of the lift force at higher Strouhal numbers.